Calling for an Integrated Computational Systems Modelling Framework for Life Cycle Sustainability Analysis - Marvuglia, Antonino; Benetto, Enrico; Murgante, Beniamino (Journal of Environmental Accounting and Management, 2026)
The implementation process of sustainable development goals poses considerable challenges to policy makers, as well as to scientists. This requires improving the knowledge on linkages between the key types of resources, the resources and the environment and the resources and the economy. The underlying challenges are inherently integrated and shall be pursued in combination. This calls for an integrated approach, which still suffers of a lack of cohesion in quantitative sustainability assessment tools and cooperation among different disciplines. A conceptual framework for life cycle sustainability analysis (LCSA) which could embrace life cycle thinking methods, stakeholders analysis supported by multicriteria decision analysis (MCDA) and dynamic system modelling has been advanced by some authors, but it still lacks of operationalization. This is the right moment to tackle this challenge because of the shared consensus on the need, added value and feasibility of creating new LCSA methodologies and tools to derive consumer information, supply chain improvements and policy support. This special issue does not present a solution for an integrated operational framework, however represents an attempt to enhance cooperation of scientists belonging to different disciplines under the overarching umbrella of a lifecycle based perspective.